Cardiomyocyte apoptosis vs autophagy with prolonged doxorubicin treatment: Comparison with osteosarcoma cells - Tacar, O.; Indumathy, S.; Tan, M.; Baindur-Hudson, S.; Friedhuber, A.; Dass, Crispin (Blackwell Publishing Ltd, 2015)
Objective Doxorubicin (Dox) is a frontline chemotherapeutic against osteosarcoma (OS) that is plagued by side effects, particularly in the heart. The specific objective of this article is to investigate whether low-dose Dox treatment had pro-autophagic effects in cardiomyocytes as well as osteosarcoma cells. Methods This study characterises apoptotic (Bax) and autophagic (Beclin-1) biomarker levels in human OS and cardiomyocyte cell lines as well as in various tissues when mice are exposed to low (1-mg/kg, thrice weekly) and high (3-mg/kg thrice weekly) dose Dox for a month. Key findings There was a decrease in Bax and increase in Beclin-1 in cardiac tissue in the high-dose group. Dox decreased Beclin-1 in the skin and liver, with no clear indication in the stomach, small intestine and testis. At low Dox doses of 10 and 100-nm in cardiomyocytes and OS cells, there is a pro-apoptotic effect, with a quicker response in the 100-nm condition, and a slower but steady increase of a pro-apoptotic response at the lower 10-nm dose. However, electron microscopy images revealed changes to human OS cells that resembled autophagy. Human prostate, breast and colorectal cells treated with 10-nm Dox showed ~ 40% reduction in cell viability after 24-h. Conclusion In culture, cells of both cardiomyocytes and OS revealed a predominant pro-apoptotic response at the expense of autophagy, although both seemed to be occurring in vivo.